2011
DOI: 10.1021/ma200231a
|View full text |Cite
|
Sign up to set email alerts
|

Isotactic Polypropylene with (3,1) Chain-Walking Defects: Characterization, Crystallization, and Melting Behaviors

Abstract: Using two living nickel α-diimine complexes (rac-1 and rac-4) activated with methylaluminoxane (MAO), isotactic polypropylene (iPP) samples containing five types of regiodefects were synthesized. Both isolated and successive groups of (2,1) and (3,1) enchainments were identified by solution-state 13C NMR spectroscopy. The extended monomer and bulky nature of these defects add some restraints to the crystallinity level that can be achieved in these polymer samples. The complex based on a cumyl-derived ligand, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 76 publications
0
44
0
Order By: Relevance
“…The i ‐PP backbone defect types can be divided into conventional stereodefects, and 2,1 and 3,1 regiodefects. The Z‐N and metallocene i ‐PPs usually show the stereodefects, whereas late Ni diamine catalysts, because of the chain walking property, generate both defect types . Some commercial metallocene i ‐PPs have also been reported to exhibit either defect type .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The i ‐PP backbone defect types can be divided into conventional stereodefects, and 2,1 and 3,1 regiodefects. The Z‐N and metallocene i ‐PPs usually show the stereodefects, whereas late Ni diamine catalysts, because of the chain walking property, generate both defect types . Some commercial metallocene i ‐PPs have also been reported to exhibit either defect type .…”
Section: Resultsmentioning
confidence: 99%
“…The butyl branch of a propylene‐1‐hexene statistical copolymer, unlike the pendant ─CH 3 in i ‐PP, is knowingly excluded from the crystalline region. Therefore, if the regiodefect i ‐PP shows a comparable or lower melting point and crystallinity than the reference propylene‐1‐hexene copolymer, the following can be concluded: The above defects are random and they exclude the crystalline region. They can be regarded as co‐units that impart a copolymer characteristic to the i ‐PP chain. Flory's thermodynamic exclusion equilibrium theory will also apply to regiodefect i ‐PP …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We initially selected Ni precatalyst C1 (Chart ), which was chosen based on its reported living, chain‐growth olefin polymerization behavior as well as its ability to synthesize P3HT with a targeted number‐average molecular weight ( M n ) and moderate dispersity (Đ) . Due to the high sensitivity of the olefin polymerization to coordinating substrates, including thiophene and THF, we synthesized the polyolefin block first, followed by polythiophene.…”
Section: Resultsmentioning
confidence: 99%
“…[15] Analysis of the obtained polymer by 13 CNMR spectroscopy revealed that the control over regioregularity was almost absolute. [16,17] According to our preliminary theoretical calculations, [18] the high regioregularity can be attributed to the selective 1,2-insertion of propylene.I ti s worth noting that other, previously reported, propylene polymerization catalysts based on Group 10 metals,f or example,n ickel complexes, [19,20] require low temperatures (< À60 8 8C) to achieve control over the regioregularity. Moreover,the stereoregularity of the polypropylene obtained with 1d (entry 4) was much improved (mm = 0.49; Figure 1b) relative to that obtained with 1a or 1c (entries 1or3).…”
mentioning
confidence: 99%